KERJASAMA PENANGGULANGAN RISIKO PENULARAN COVID-19 KEWILAYAHAN DI KECAMATAN IBUN KABUPATEN BANDUNG - Dicky Darsono Eka Putra; Asep Sumaryana; Ramadhan Pancasilawan (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The score of 1.63 makes Bandung Regency an area with a high risk of Covid transmission. The compacted value is based on the growth of new clusters in the community with a small scope. The condition of the Bandung district is not good and tends to get worse. Responding to cases requires community involvement with community participation, especially through community institutions. However, with the many aktors involved, it is difficult to carry out Partnership, especially the temporary regional task force and flexible organization. The purpose of this research is to describe the process of Partnership that occurs in the regional task force in Ibun sub-district. Collaborative research in managing the risk of Covid transmission using qualitative methods with a descriptive approach. Methods of collecting data using interviews, observations and literature that are adjusted to the data taken. The analysis technique is through triangulation of data and sources. The results of the research are the Partnership carried out by the regional task force in Ibun subdistrict with the variation of the work relationship process from the regional task force, Partnership is more effective and everyone can carry out work relationships according to the needs of the Partnership. However, several problems were found, such as lack of initiative, lack of awareness, and pandemic burn out that affected the psychological aspect, so it can be concluded that the Partnership between the regional task force in tackling has been carried out well but has not been maximized, because it is very difficult to manage the collaboration process when faced with multiple aktors. and implemented at the community level.   Keywords         : Partnership, Covid Management, Regional Task Force